A comprehensive assessment of immunophenotyping performed in cryopreserved peripheral whole blood. Issue 5 (22nd May 2017) - Verschoor, Chris P.; Kohli, Vikas; Balion, Cynthia
Abstract : Background: Monitoring the frequency and phenotype of white blood cell subsets using flow cytometry (immunophenotyping) has proven to be an incredibly powerful tool in the assessment of health. Although improved technologies have aided in the practical implementation of immunophenotyping in clinical and epidemiological studies, the transportation of blood from the site of collection to a central laboratory for analysis within a reasonable timeframe may not be feasible. Hence, the purpose of the following study was to investigate the validity of cryopreserved whole blood as a simple to prepare and cost‐effective biospecimen for multi‐colour immunophenotyping in a large epidemiological study—namely, The Canadian Longitudinal Study on Aging (CLSA). Methods: In fresh and cryopreserved blood and cryopreserved peripheral blood mononuclear cells (PBMCs) we measured cellular viability and the quantities (absolute counts and relative frequencies) of total leukocytes, neutrophils, monocytes, CD4/CD8 T‐lymphocytes, B‐lymphocytes, natural killer (NK) cells, NKT cells, plasmacytoid dendritic cells (pDCs), and basophils. Results: Estimates obtained from immunophenotyping in cryopreserved blood were comparable to fresh blood (Avg. rho: absolute cell counts = 0.71, frequency relative to CD45 leukocytes = 0.84, frequency relative to PBMCs = 0.86), cryopreserved PBMCs (0.86), and complete blood counts by hematological analyzer (0.71) and exhibited good intra‐ and inter‐assay precision (Avg. CV = 4% and 3%, respectively). Conclusions: Given this, cryopreserved blood should be considered a feasible biospecimen in clinical and epidemiological studies requiring leukocyte immunophenotyping. © 2017 International Clinical Cytometry Society